2011
DOI: 10.1103/physrevd.84.105005
|View full text |Cite
|
Sign up to set email alerts
|

Summing planar diagrams by an integrable bootstrap

Abstract: Correlation functions of matrix-valued fields are not generally known for massive renormalized field theories. We find the large-N limit of form factors of the (1 + 1)-dimensional sigma model with SU(N) × SU(N) symmetry. These form factors give a correction to the free-field approximation for the N = ∞ Wightman function. The method is a combination of the 1/N-expansion of the S-matrix and Smirnov's form-factor axioms. We expand the renormalized field in terms of a free massive Bosonic field as N → ∞.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…It has been shown that the form factors of operators are not trivial at large N [3][4] [5]. As we will see, the computation of thermal expectation values can be done by summing over form factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the form factors of operators are not trivial at large N [3][4] [5]. As we will see, the computation of thermal expectation values can be done by summing over form factors.…”
Section: Introductionmentioning
confidence: 99%
“…In Section III, we build on earlier results [4], [5], [6] to find all the form factors of the current operator. We use these to write down an expression for the vacuum expectation value of two currents in Section IV.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the conventional wisdom concerning the 't Hooft limit can be tested. For example, the operators defining the Zamolodchikov-Faddeev algebra have been identified with a free Gaussian master field [4], from which the scaling field and other operators can be constructed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations